MicroRNAs are associated with blood-pressure effects of exposure to particulate matter: Results from a mediated moderation analysis - Motta, Valeria (Environ Res, 2016)
AIMS: Exposure to particulate air pollution is associated with increased blood pressure (BP), a well-established risk factor for cardiovascular disease. To elucidate the mechanisms underlying this relationship, we investigated whether the effects of particulate matter of less than 10 μm in aerodynamic diameter (PM(10)) on BP are mediated by microRNAs. METHODS AND RESULTS: We recruited 90 obese individuals and we assessed their PM(10) exposure 24 and 48 h before the recruitment day. We performed multivariate linear regression models to investigate the effects of PM(10) on BP. Using the TaqMan® Low-Density Array, we experimentally evaluated and technically validated the expression levels of 377 human miRNAs in peripheral blood. We developed a mediated moderation analysis to estimate the proportion of PM(10) effects on BP that was mediated by miRNA expression. PM(10) exposure 24 and 48 h before the recruitment day was associated with increased systolic BP (β=1.22 mmHg, P=0.019; β=1.24 mmHg, P=0.019, respectively) and diastolic BP (β=0.67 mmHg, P=0.044; β=0.91 mmHg, P=0.007, respectively). We identified nine miRNAs associated with PM(10) levels 48 h after exposure. A conditional indirect effect (CIE=−0.1431) of PM(10) on diastolic BP, which was mediated by microRNA-101, was found in individuals with lower values of mean body mass index. CONCLUSIONS: Our data provide evidence that miRNAs are a molecular mechanism underlying the BP-related effects of air pollution exposure, and indicate miR-101 as epigenetic mechanism to be further investigated.